MOTIVASI DAN HARAPAN PERAWAT MENJADI PERAWAT TENAGA KERJA SUKARELA - Royani, Hotma; Antoni, Adi (Jurnal Kesehatan Ilmiah Aufa Royhan, 2017)
voluntary nurses are the nurses who provide health care voluntarily without expecting any fee. The objective of the research was to explore deeply motivations and nurses expectation being voluntary nurses. The research used phenomenological design. The data were gathered by conducting in-depth interviews. Purposive sampling technique was used to select the participants who had met the criteria. They consisted of 10 voluntary nurses at RSUD, Padangsidempuan. The result of the interviews was recorded and analyzed by using content analysis. The result of the research showed that there were five themes which reflected the research phenomena. They were increasing knowledge, increasing experience, choosing being a voluntary nurse than being jobless, getting new friend, getting attention from hospital, and getting attention from government. It is recommended that the government should pay attention to TKS nurses